Paraneoplastic Pemphigus Associated With Lung Cancer: A Case Report - Ozcan, Hamdi; Gunen, Hakan; Turker, Gamze; Dogan, Gursoy (Annals of Medical Research, 2021)
None
Keywords: Lung Cancer, Paraneoplastic Pemphigus, Diagnosis